2023
DOI: 10.3389/fgene.2023.1064924
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for lysosomal storage diseases: Current clinical trial prospects

Abstract: Lysosomal storage diseases (LSDs) are a group of metabolic inborn errors caused by defective enzymes in the lysosome, resulting in the accumulation of undegraded substrates. LSDs are progressive diseases that exhibit variable rates of progression depending on the disease and the patient. The availability of effective treatment options, including substrate reduction therapy, pharmacological chaperone therapy, enzyme replacement therapy, and bone marrow transplantation, has increased survival time and improved t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…The end result is tissue destruction in lysosomal storage disease. Studies have demonstrated a comprehensive understanding of current approaches (e.g., gene therapy, enzyme replacement therapy, substrate reduction therapy, hematopoietic stem cell transplantation, pharmacological chaperone therapy, and the proteostasis regulators) for the management of complications of lysosomal storage diseases [ 205 , 206 , 207 , 208 , 209 ]. However, the current treatment experiences difficulty targeting the pathologic organs, including the CNS, PNS, retina, and skeletal system.…”
Section: Discussionmentioning
confidence: 99%
“…The end result is tissue destruction in lysosomal storage disease. Studies have demonstrated a comprehensive understanding of current approaches (e.g., gene therapy, enzyme replacement therapy, substrate reduction therapy, hematopoietic stem cell transplantation, pharmacological chaperone therapy, and the proteostasis regulators) for the management of complications of lysosomal storage diseases [ 205 , 206 , 207 , 208 , 209 ]. However, the current treatment experiences difficulty targeting the pathologic organs, including the CNS, PNS, retina, and skeletal system.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their limitations, ERTs for Gaucher Disease [16], Fabry Disease [17], Acid Lipase Deficiency [18], Ceroid lipofuscinosis type 2 [19], Niemann-Pick diseases type A/B [20] , α-Mannosidosis [21], and MPS I, II, IV, VI, and VII [22] are, nowadays, a reality and numerous patients have benefited from them over the last decades. Additional clinical trials with novel enzymes and alternative delivery routes are also ongoing [23]. Overall, ERT is not a cure, but it does significantly increase enzyme activity in many disorders, thus improving their associated clinical symptoms [24].…”
Section: Lysosomal Storage Diseasesmentioning
confidence: 99%
“…While LSDs are typically challenging to treat, several strategies for disease management have emerged. These include enzyme replacement therapy (ERT), [6] gene therapy (GT), [7,8] substrate reduction therapy (SRT) [9] and the chaperone-mediated therapy (CMT). [10 -16] Within the group of LSDs, Morbus Gaucher stands out as the most frequently observed one, with an estimated global prevalence of 1 : 50,000 to 1 : 100,000.…”
Section: Introductionmentioning
confidence: 99%
“…While LSDs are typically challenging to treat, several strategies for disease management have emerged. These include enzyme replacement therapy (ERT), [6] gene therapy (GT), [7,8] substrate reduction therapy (SRT) [9] and the chaperone‐mediated therapy (CMT) [10–16] …”
Section: Introductionmentioning
confidence: 99%